DIPLOMASI TIMOR LESTE BERGABUNG DALAM KEANGGOTAAN TETAP ASEAN - Syifa Ayunda Swastia; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research explain about Timor Leste Wants to Join ASEAN Membership, This is an opportunity to improve the country 's profile in the region in addition to economic and political advantages which can be obtained by becoming a member of ASEAN. since Timor Leste applied to join the members of asean untill recently Timor leste has not been accepted as an ASEAN memberhip. One of ASEAN membershipa assume Timor Leste can’t be a membership of ASEAN because the gap with the other Asean member countries it feared would be problem fo ASEAN.This research theoretically has built by using Morghenthau Neoclassical Realism perspective on International Relationsand supported by Foreign Policy theory from James N. Rossenau. Formulation of all arguments, data, facts, and theoritical framework in this research using qualitative explanation methods.This research also using nation-state as the level of analyze, the focus on this research Timor Leste in diplomatic efforts became a membership of asean.To accepts Timor Leste doing diplomacy to of ASEAN membership. Timor Leste interlacing good relationship with membership of ASEAN. Timor Leste doing collaboration with ASEAN’s membership, then Timor Leste join all ASEAN activity and Timor Leste Also intituiting ASEAN office in Dili, Timor Leste. that aptly been accepted Timor Leste must more tries to get support to joining to be a membership of ASEAN.Keywords: ASEAN, Timor Leste, Timor Leste Diplomacy’s, Timor Leste wants to join membership of ASEAN’s.